2023
DOI: 10.1038/s41467-023-38089-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface-localized CsgF condensate is a gatekeeper in bacterial curli subunit secretion

Abstract: Curli are functional amyloids present on the outer membrane of E. coli. CsgF is required for the proper assembly of curli. Here, we found that the CsgF phase separates in vitro and that the ability of CsgF variants to phase-separate is tightly correlated with CsgF function during curli biogenesis. Substitution of phenylalanine residues in the CsgF N-terminus both reduced the propensity of CsgF to phase-separate and impaired curli assembly. Exogenous addition of purified CsgF complemented csgF − cells. This exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…6365 B. cereus is phylogenetically related to B. subtilis ; however, we suggest that the polymerization of CapP-CalY-TasA amyloid pili is more closely related to the amyloid curli system of E. coli and Salmonella spp. than to the TasA-TapA system of B. subtilis 6671 . Building upon the novel insights unveiled in this study and the current knowledge on pili polymerization, we propose a revised model for the assembly of biofilm-specific pili in B. cereus (see Graphical abstract), which involves the paralogous proteins TasA and CalY, as well as the biofilm-specific protein CapP.…”
Section: Discussionmentioning
confidence: 98%
“…6365 B. cereus is phylogenetically related to B. subtilis ; however, we suggest that the polymerization of CapP-CalY-TasA amyloid pili is more closely related to the amyloid curli system of E. coli and Salmonella spp. than to the TasA-TapA system of B. subtilis 6671 . Building upon the novel insights unveiled in this study and the current knowledge on pili polymerization, we propose a revised model for the assembly of biofilm-specific pili in B. cereus (see Graphical abstract), which involves the paralogous proteins TasA and CalY, as well as the biofilm-specific protein CapP.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies shown that both fimB and fimE were responsible for controlling the expression of type I fimbriae in E. coli ( 95 97 ). Swasthi et al ( 98 ) reported that curli were functional amyloids present on the outer membrane of E. coli , while csgB and csgF were required for curli assembly ( 98 ). Four genes (sfaY, sfaE, sfaF, and sfaG) were known to play a vital role in the adhesion of S-fimbriae in the pathogenesis of E. coli meningitis ( 99 ).…”
Section: Discussionmentioning
confidence: 99%